Stronger cooling effects of transpiration and leaf physical traits of plants from a hot dry habitat than from a hot wet habitat - Lin, Hua; Chen, Yajun; Zhang, Houlei; Fu, Peili; Fan, Zexin (Functional ecology, 2017)
Leaf temperature exerts an important impact on the microenvironment and physiological processes of leaves. Plants from different habitats have different strategies to regulate leaf temperature. The relative importance of physical traits and transpiration for leaf temperature regulation in the hot habitat is still unclear. We investigated 22 leaf physical traits, transpiration, and thermal properties of 38 canopy species of seedlings in a greenhouse, including 18 dominant species from a hot wet habitat (HW) and 20 dominant species from a hot dry habitat (HD). To separate the impact of transpiration and leaf physical traits on leaf temperature, we measured the diurnal courses of leaf temperatures with and without transpiration. The temperature of a reference leaf beside each individual was measured simultaneously to render temperatures comparable. Generally, the species from HD showed lower leaf temperatures than the species from HW under the same conditions. Both transpiration capacity and cooling effect of leaf physical traits were stronger for the plants from HD. Active transpiration provides a suitable thermal environment for photosynthesis, while xeromorphic leaves can dampen heat stress when transpiration is suppressed. Higher vein density and stomatal pore area index (SPI) facilitated higher transpiration capacity of the plants from HD. Meanwhile, shorter leaves and thinner lower epidermis of the plants from HD were more efficient in heat transfer, although relationships were much weaker than the synergic effect of all the physical traits. Our results confirmed that transpiration and leaf physical traits provided double insurance for avoiding overheating, particularly for plant from HD. We emphasize that transpiration is a more effective way to cool leaves than physical traits when water is sufficient, which may be an important adaptation for plant from HD where rainfall is sporadic. Our results provide further insight into the relationship between physical traits and transpiration for the regulation of leaf temperature, and the co‐evolution of gas exchange and thermal regulation of leaves. A plain language summary is available for this article. Plain Language Summary